Effect of Various Irrigation Regimes and Nitrogen Fertilizer on Yield and Water Use Efficiency in Soybean (Glycin Max) - Chafi, Ali Arezoomand; Amiri, Ebrahim; Gohari, Ali Abdzad (International Journal of Natural Sciences Research, 2014)
An experiment was conducted to evaluate the Effects of water infiltration to soil in yield and water use efficiency in soybean (Glycin max) in Langeroud, North of Iran. The study was done on a split plot in a complete random block plan with 3 replications in the 2011 crop year. In this pilot study, a randomized complete block design with a split plot design and 3 replications was carried out in the field. Each plot had a dimension of 2×5 meters and 7 rows respectively. The main factor management without irrigation (rainfed) and irrigated with a period of 6, 12 and 18 days, and nitrogen fertilizer treatments consisted of 0, 30, 60, 90 and 120 were considered as sub plots. Different levels of irrigation and nitrogen fertilization on the yield and interaction between them, pods significant at the 5% level were reported. 12 days to a yield maximum of Irrigation Management 5125.6 kg per hectare, respectively. The lowest seed yield without fertilizer at 3888.1 kg/ha was but with increasing fertilizer significantly increased seed yield. The level of 90 kg.N/ha, the maximum yield of 4228.1 kg per hectare was obtained. The highest pod yield of 12 day irrigation management with the 5312.3 kg per hectare was obtained. The highest pod yield was of 90 kg per ha of nitrogen was increased from 90 to 120 kg of nitrogen reduced pod yield from 5438.3 to 4804 kg/ha.